Breakthrough studies of Co₃O₄ supported activated carbon monolith for simultaneous SO₂/NOx removal from flue gas - Wan Ab Karim Ghani, Wan Azlina; Silas, Kiman; Choong, Thomas Shean Yaw; Rashid, Umer (Elsevier, 2018)
This work investigates the deposition precipitation, pore volume impregnation and hydrothermal methods of synthesizing activated carbon monolith supported metal oxide adsorbent (Co₃O₄/ACM). The hydrothermally synthesized Co₃O₄ activated carbon monolith adsorbent (Hm-Co₃O₄/ACM) demonstrate better adsorption capacity (SO₂ is 123.1, NOx is 130.2 mg/g) than the adsorbents synthesized by the other methods. The adsorbent displayed high affinity to NOx adsorption where this influence was associated to operation conditions, physical and chemical properties of the adsorbent which were expressed in the plot of the breakthrough curve. Moreover, the surface properties (BET), thermal decomposition (TGA), functional groups (FTIR), chemical composition (XRD) and surface morphology (FESEM) of the adsorbent were investigated. The Langmuir adsorption isotherm fitted the experimental results meanwhile, the thermal regeneration of the adsorbent over two cycles showed an average regeneration efficiency of 94.4% for SO₂ and 94.8% for NOx. Finally, the post regeneration characterization analyses were discussed.